Profil Kompetensi Pedagogik Calon Guru SD Dalam Pembelajaran Matamatika - Hidayat, Rosidah Aliim; Wijayanto, Zainnur; Rhosyida, Nelly; Jarapa, Amelia A; Dharmawan, Pramudya Anta (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
The curriculum structure at the elementary school level is characterized by significant variability, which necessitates that educators and teachers possess a comprehensive understanding of the essential competencies involved. One of the fundamental competencies closely related to student learning is pedagogical competence. This research is a quantitative descriptive survey study. This study aims to analyze the profile of the pedagogical competence of prospective elementary school teachers in teaching mathematics. The subjects of this study consisted of 64 individuals selected using random sampling. The analysis results of the pedagogical competence profile of prospective elementary school teachers in teaching mathematics generally showed a reasonably competent outcome, with an average score of 4.37. These results indicate that each prospective elementary school teacher already possesses a sufficient foundation of competence to develop classroom learning activities. This is because pedagogical competence prioritizes the ability to manage the classroom, understand students, and comprehend the assessment needs given to students.